Minskning av vibrationer i mobila plansvarvmaskiner - Falk, William; Karlsson, Nils (My University, 2023)
The study, conducted in collaboration with Metalock Engineering, investigates the vibrations characteristics of the Mirage MM1000i mobile machine, with the objective of a better understanding of machine vibrations, identifying critical components causing vibration and proposing design modifications to mitigate these vibrations. The analysis combines physical vibrations measurements and Finite Element (FE) simulations to discern the natural frequencies of the machine. A comparison of these analyses enabled the localization of components where machine vibrations showed the strongest resonance, which contributes to the understanding of the relation between critical components with machine vibrations. The results highlight the swing arm and counterweight arm as crucial components for vibration minimization. Based on these findings were concept solutions developed, which primarily involved structural modifications of these components to increase their stiffness and reduce their mass, leading to reduced machine vibrations. This study lays the groundwork for a new machine concept with a lower risk of vibration and chatter, potentially enhancing productivity.
Keywords: Machine Vibrations; Modal Analysis; Finite Element Method; Machine Design